STUDENTS’ ATTITUDE AND PERCEPTION TOWARD INDEPENDENT LISTENING USING LISTENING LOG (RETAIN, 2020)
Many ways could be done to improve listening skills in learning English. Not only through formal classes activity, but also through out-of-class independent learning. Conducting a listening log is considered as an independent learning activity that can improve students’ listening skills. Therefore, this research aimed to find out how the students are conducting independent listening using listening logs and to describe students’ perceptions towards the activity. The subject of this study were twenty-three students in the Academic Listening C class in UNESA, which divided into three levels of students who are high, middle, and low achievers. To collect the data, the researcher used a semi-structured interview. The data were analyzed qualitatively by applying three stages; familiarizing & organizing, coding & reducing, and interpreting & representing. The results of the study showed that there is no significant difference between high, middle, and low achievers. Most of the participants showed almost the same response. Based on participants’ answers, conducting listening logs is fun and diverting as an independent listening activity. By keeping listening logs, the students also gain many benefits such as becoming aware of their learning, acquiring new knowledge, learning new vocabularies, and improving their listening skills. However, some students considered keeping listening logs is boring as their independent listening activity. Keywords: listening, independent listening, listening log